Revisión teórica de la técnica de radares de dispersión incoherente y su conexión con las ecuaciones diferenciales estocásticas - La Rosa La Rosa, Brian Humberto (Pontificia Universidad Católica del Perú, 2021)
The Incoherent Scatter Radar (ISR) technique provides an important tool for ionospheric plasma parameter estimation through the calculation of the electron density spectrum. This quantity is constrained to the ionospheric approximations considered. If these are very realistic, finding an analytical expression for the terms involve in the electron density spectrum could be impossible. In that sense, using the mathematical tool known as stochastic differential equation (SDE) is required. Because of the nature of the equation described the ionospheric particle dynamics, called Langevin equation, stochastic numerical methods have to be studied. In this work, we will present a review of ISR theory and the connection to SDE. Moreover, we list three different methods, which are used to analyze the collisional and magnetized approximation of the ionosphere.
Keywords: Radar; Plasmas espaciales; Análisis estocástico; http://purl.org/pe-repo/ocde/ford#1.03.00